Interunion Conflict and the Evolution of Faculty Unionism in Canada - Ross, Stephanie; Savage, Larry (Studies in Political Economy, 2020)
This article explores the role of interunion conflict in the rise and evolution of faculty unionism in Canada. We argue that competition and tension between the Canadian Association of University Teachers (CAUT) and the Canadian Union of Public Employees (CUPE) in the early 1970s played a key role in driving professors’ support for the certification of independent faculty associations. Moreover, we contend that a parochial, sectionalist, and craft-like brand of faculty unionism remained dominant in Canada until the 2000s, when external forces and the rise of the neoliberal university convinced CAUT’s leadership to broaden the tent in terms of membership and embrace an enlarged notion of solidarity in an effort to better defend terms and conditions of work for university teachers.